ANALISIS FAKTOR PENYEBAB EKSTERNAL DAN INTERNAL KEBANGKRUTAN EASTMAN KODAK COMPANY - Maylinasari, Lely; Meisaputri, Ratna; Fahmi, Fiqih Zulfikar; Firky, Alfandio (Journal of Digital Business and Innovation Management, 2022)
Analysis of the factors that influence customer satisfaction using Eastman Company Tow Matrix analysis, External Factor Evaluation analysis is used to determine the company's external factors related to opportunities and threats. This analysis aims to find out and analyze what factors are opportunities and threats that will be faced by the company using Tows, EFE, IFE analysis. The method used in the analysis process is the Tows, EFE, IFE process by using a predetermined table. The results show that sequentially the analysis used affects the company using Tows analysis, EFE, IFE are Opportunities, Threads, Strengths, Weaknesses. Therefore the analysis that affects the company can develop. Keywords: customer satisfaction; Eastman Company's Tow Matrix analysis; EFE; IFE